Antiradical and Cytotoxic Activities of Varying Polarity Extracts of the Aerial Part of Euphorbia hirta L. - Shanmugapriya Perumal; Roziahanim Mahmud; Suthagar Pillai Piaru; Wei Cai Lee; Surash Ramanathan (Journal of Chemistry)
Euphorbia hirta is a well-known ethnomedicinal plant with diverse biological activities. The aim of the present study is to investigate the antiradical activities of various solvent extracts of the aerial part of E. hirta as well as to determine the possible cytotoxicity of these extracts. The aerial part of E. hirta was extracted with different solvent systems in order to increase polarity. The solvents used were hexane, dichloromethane (DCM), ethyl acetate (EA), ethanol (EtOH), and methanol (MeOH). The contents of total phenols and total flavonoids were analyzed by UV spectrophotometry, whereas the potential free radical-scavenging activities of the extracts were evaluated using the stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), the β-carotene-linoleic acid bleaching system, and reducing power. The EtOH extract exhibited the highest total phenolic content (237.9±2.26 mg GAE/g), and DCM extract scored the highest total flavonoid content (121±0.15 mg CE/g). The MeOH extract showed a potent free radical-scavenging activity as evidenced by low EC50 at 42.81 µg/mL. Interestingly, the EtOH extract demonstrated the highest reducing power activity with EC50 value of 6.18 µg/mL. In β-carotene-linoleic acid assay, oxidation of linoleic acid was effectively inhibited by DCM extract with 96.15±0.78%. All the extracts showed no cytotoxic activity against Vero cells.